A Reevaluation of Superior Tree Performance After 48 Years for a Loblolly Pine Progeny Test in Southern Arkansas - Bragg, Don C. (Frontiers in Forests and Global Change, 2021)
A plus-tree progeny test of full- and half-sib “superior” loblolly pine (Pinus taeda) was installed in 1969 on the Crossett Experimental Forest (CEF) to consider the performance of 28 improved families with unimproved planting stock from the CEF (family W29). Performance was evaluated using data from young (3-year-old; early 1970s), maturing (25-year-old; 1994), and mature (48-year-old; 2017) trees. With the exception of a single improved family, early survival was high (>80%), with most families exceeding 90%. Three years post-planting, fusiform rust infection rates were also low, with most families having less than 1% of seedlings infected. At this early stage, the unimproved CEF family W29 only slightly underperformed the best full- and half-sib superior families. By 1994, W29 had slightly higher than average merchantable volume. This trend continued for W29 when remeasured in 2017, with the average merchantable volume yield for W29 statistically similar to the most productive families. This study found only limited volume performance gains from crossing plus-trees. However, it was important to note that several of the best height growth-performing families in 1972 were not the highest merchantable volume producers at 25 or 48 years, and some of the worst early performers moved into the upper tiers by the later remeasurements. These outcomes suggest that depending solely on early height performance to select families for long-term (>50 year) volume (especially if adjusted for wood density) or biomass yields may not be the best approach for forest managers seeking to increase carbon sequestration.